The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10157-009-0158-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal allograft tuberculosis: report of three cases and review of literature

Abstract: Renal transplant recipients are prone to a variety of infections due a persistent immunodepleted state. Incidence of tuberculosis in this population is much higher compared with the general population. While pulmonary tuberculosis still remains the commonest form in this population, renal allograft tuberculosis is very rare. We report two cases of isolated allograft tuberculosis and one case of allograft tuberculosis with coexistent pleuro-pulmonary and bone marrow involvement. All three cases had presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
15
3
Order By: Relevance
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9% in the literature [4,[25][26][27]. Impairment of the general state was observed in 31,2% patients in our study versus 40% in literature [27,28].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9% in the literature [4,[25][26][27]. Impairment of the general state was observed in 31,2% patients in our study versus 40% in literature [27,28].…”
Section: Discussioncontrasting
confidence: 43%
“…Anti-TB treatment can induce a successful management with reduction of allograft nephropathy, graft nephrectomy, and mortality [2,25,53,54]. Response to antiTB treatment should be considered to make a diagnosis among patients highly suspected of TB infections.…”
Section: Discussionmentioning
confidence: 99%
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9 % in literature [4,25,26,27]. Impairment of the general state was observed in 31,2% patients in our study versus 40 % in literature [27,28].…”
Section: Disscussioncontrasting
confidence: 42%
“…The allograft biopsy is helpful when other investigations are inconclusive with symptoms of allograft dysfunction [2]. Histology shows, in this form, granuloma suggestive of TB [2,25,39].…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation